Endocytic control of ion channel density as a target for cardiovascular disease - Robertson, Gail A. (American Society for Clinical Investigation, 2009)
Ion channels encoded by the human ether-a-go-go-related gene (HERG) give rise to the rapidly activating delayed rectifier K(+) current (I(Kr)), the perturbation of which causes ventricular arrhythmias associated with inherited and acquired long QT syndrome. Electrolyte imbalances, such as reduced serum K(+) levels (hypokalemia), also trigger these potentially fatal arrhythmias. In this issue of the JCI, Guo et al. report that physiological levels of serum K(+) are required to maintain normal HERG surface density in HEK 293 cells and I(Kr) in rabbit cardiomyocytes. They found that hypokalemia evoked HERG channel ubiquitination, enhanced internalization via endocytosis, and ultimately degradation at the lysosome, thus identifying unbridled turnover as a mechanism of hypokalemia-induced arrhythmia. But too little channel turnover can also cause disease, as suggested by Kruse et al. in a study also in this issue. The authors identified mutations in TRPM4 — a nonselective cation channel — in a large family with progressive familial heart block type I and showed that these mutations prevented channel internalization (see the related articles beginning on pages 2745 and 2737, respectively).